Effect Of Vibration Frequency On Naca 4412 Airfoil Aerodynamic Performance - Chan, Ze Yu (Universiti Sains Malaysia, 2019)
Vibration is due to the aeroelastic stability of a typical section airplane wing NACA 4412 which finishes in general by the breaking of the plane, it can be determined as a dynamic instability of the structure. As vibration might lead to catastrophe, it is very important to understand the effect of vibration frequency on an airfoil aerodynamic performance. Thus, this project was designed to obtain the aerodynamic characteristics on NACA 4412 airfoil at different vibration frequencies and to study the aerodynamic characteristics on NACA 4412 airfoil at different Reynolds numbers. The experiment was conducted at two different cases, one by using a rigid airfoil without vibration motor attached on it while another case is by using a vibrating airfoil. As known, the performance of an aircraft wing depends mostly on the aerodynamic characteristics such as the lift force, drag force and etc. In this paper, experiment will be conducted in turbulent flow with Reynolds numbers (17 000, 27 000, 34 000, 46 000 and 57 000) at different angles of attack (0°, 10°, 20°, and 30°) for the two cases mentioned. For the case of using vibration motor, the vibration frequency applied to the airfoil model is varied by the number of rotation of the vibration motor used to the induce vibration. The results will be recorded and plotted to observe how the lift-to-drag ratio of the NACA 4412 airfoil model vary with different vibration frequencies. The effect of varying Reynolds numbers on the aerodynamic characteristics was also investigated in both cases.